2004
DOI: 10.1007/s10633-004-8056-4
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and functional changes of the macula after vitrectomy and creation of posterior vitreous detachment in eyes with diabetic macular edema

Abstract: The purpose of this study was to determine the morphological and functional changes in the macula after pars plana vitrectomy with the creation of a posterior vitreous detachment in eyes with diabetic macular edema (DME). A simple posterior vitreous detachment was created during pars plana vitrectomy accompanied by simultaneous cataract surgery in 19 eyes of 17 patients with DME. The visual acuity (log MAR units), multifocal electroretinograms (mfERGs), and optical coherence tomographically (OCT)-determined fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…We have examined the macular function by using multifocal electroretinography (mfERG), and found that the electrical responses obtained from the macular area were also significantly correlated with the foveal thickness. 11,12 The results indicated that the mfERGs may provide an objective method to evaluate and assess DME.…”
Section: Discussionmentioning
confidence: 95%
“…We have examined the macular function by using multifocal electroretinography (mfERG), and found that the electrical responses obtained from the macular area were also significantly correlated with the foveal thickness. 11,12 The results indicated that the mfERGs may provide an objective method to evaluate and assess DME.…”
Section: Discussionmentioning
confidence: 95%
“…Terasaki et al (66) found improved vision and electroretinographic activity and thinning of retina following vitrectomy in patients with diabetic macular edema. Yamamoto et al (67) proposed that the creation of a posterior vitreous detachment is critical in order to influence diabetic macular edema through vitreous surgery. In all reports there is structural improvement of macular edema following vitrectomy, but visual improvement is variable and in some cases either minimal or transient (60,68,69).…”
Section: Diabetic Macular Edemamentioning
confidence: 99%
“…Similar findings were observed in two other studies on DMO patients who had undergone vitrectomy with the creation of a posterior vitreous detachment. 11,12 We assessed the macular function by multifocal electroretinography (mfERG) and found that the electrical responses obtained from the macular area were also significantly correlated with the FT. 11 In that electrophysiological study, we examined the macular mfERG from the central 10 degrees along with the VA and OCT-determined FT. Although the VA improved significantly and the FT was reduced significantly at 6 months postoperatively, the amplitude of the mfERGs did not show any significant change, and only the peak latency of the macular response decreased significantly.…”
mentioning
confidence: 99%
“…Although the VA improved significantly and the FT was reduced significantly at 6 months postoperatively, the amplitude of the mfERGs did not show any significant change, and only the peak latency of the macular response decreased significantly. 12 It was concluded that the recovery of the macular electrical response might be limited to the shortening of the implicit time because of the severely depressed macular function due to the chronic oedema.…”
mentioning
confidence: 99%